Fibrinolysis and Coagulation in Patients with Infectious Disease and Sepsis - Philippé, J; Offner, F; Declerck, P J; Leroux-Roels, G; Vogelaers, D; Baele, G; Collen, D (Thrombosis and Haemostasis, 1991)
Sepsis is often associated with hemostatic dysfunction. This study aimed to relate changes in fibrinolysis and coagulation parameters to sepsis and sepsis outcome. Urokinase-type plasminogen activator (u-PA) antigen, tissue-type plasminogen activator (t-PA) antigen and activity, plasminogen activator inhibitor (PAI) type 1 antigen, PAI activity, antithrombin (AT) III activity, and protein C activity were measured in 24 patients suffering from sepsis or septic shock and the results were compared with those observed in 30 non-sepsis patients with severe infectious disease. The u-PA level was markedly increased in plasma of sepsis patients as compared to non-sepsis patients (11.5 ± 9.4 versus 1.6 ± 1.5 ng/ml, p <0.0001). PAI-1 antigen and t-PA activity showed a significant increase in sepsis patients (320 ± 390 ng/ml versus 120 ± 200 ng/ml, and 3.0 ± 3.6 IU/ml versus 1.0 ± 0.7 IU/ml, respectively, p <0.01). AT III was decreased in sepsis patients (58 ± 28% in sepsis versus 79 ± 26% in severe infectious disease, p <0.01) as was protein C (30 ± 18% versus 58 ± 27%, p <0.001). No significant difference was found for t-PA antigen nor for PAI activity. Nonsurvivors of sepsis were distinguished mainly by a high u-PA antigen level and increased t-PA activity. It is concluded that plasma u-PA antigen showed the strongest significant difference, among the parameters evaluated, between sepsis and severe infection. u-PA antigen may be of prognostic value in patients admitted to the medical intensive care unit for severe infectious disease.